2015
DOI: 10.1182/blood-2014-09-602573
|View full text |Cite
|
Sign up to set email alerts
|

Effects of eltrombopag on platelet count and platelet activation in Wiskott-Aldrich syndrome/X-linked thrombocytopenia

Abstract: Key Points Platelet function in WAS/XLT, measured by agonist-induced surface-activated GPIIb-IIIa and P-selectin, is proportional to platelet size. Eltrombopag increased platelet counts, but did not improve platelet activation, in most WAS/XLT patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
1
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 48 publications
0
77
1
2
Order By: Relevance
“…43,44 One study of eltrombopag in WiskottAldrich syndrome or X-linked thrombocytopenia showed improved platelet counts but persistent defects in platelet activation. 45 Although eltrombopag has been approved for use as a therapy for refractory chronic ITP in children, the authors of this study have used eltrombopag to treat severe, refractory bleeding in patients with acute ITP at the time of presentation. In this setting, eltrombopag was given to help sustain an elevated platelet count while other first-line agents were given for more immediate effect.…”
Section: Other Indications and Future Directionsmentioning
confidence: 99%
“…43,44 One study of eltrombopag in WiskottAldrich syndrome or X-linked thrombocytopenia showed improved platelet counts but persistent defects in platelet activation. 45 Although eltrombopag has been approved for use as a therapy for refractory chronic ITP in children, the authors of this study have used eltrombopag to treat severe, refractory bleeding in patients with acute ITP at the time of presentation. In this setting, eltrombopag was given to help sustain an elevated platelet count while other first-line agents were given for more immediate effect.…”
Section: Other Indications and Future Directionsmentioning
confidence: 99%
“…Recently, new thrombopoietin agonists, such as romiplostim (Nplate; Amgen, Thousand Oaks, CA, USA) and eltrombopag (Revolade; GlaxoSmithKline, Brentford, UK), have been used to treat thrombocytopenia to prevent life‐threatening bleeding while patients wait for HSCT . In particular, eltrombopag has been tested in a clinical trial (NCT00909363) in patients with WAS and XLT that reported an increase in PLT counts in the majority of patients …”
Section: Wasmentioning
confidence: 99%
“…Here we report the successful use of eltrombopag in a patient with WAS: this treatment reduced bleeding symptoms and completely eliminated the requirement for platelet transfusion. Our case adds to the literature suggesting the efficacy of eltrombopag in patients with WAS as a measure to manage profound thrombocytopenia and recurrent bleeding while awaiting definitive treatment . In particular, it may be suitable for children under the age of 2 years for whom bleeding is the first severe manifestation of WAS and may be fatal .…”
Section: Discussionmentioning
confidence: 81%
“…However, splenectomy increases the risk of severe infections, particularly after HSCT, and platelet transfusions are short‐lived, may lead to allo‐immunization, and may not be effective in all patients . Eltrombopag, a thrombopoietin (TPO) receptor agonist, is a new efficient treatment for immune thrombocytopenia in both adults and children and has been proposed also for patients with inherited thrombocytopenia . In particular, in patients with WAS, platelet production is impaired as the defective protein is essential for the polymerization of actin and proplatelets formation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation